Immunopathology of Acute Kidney Injury in Severe Malaria - Katsoulis, Orestis; Georgiadou, Athina; Cunnington, Aubrey J. (Frontiers in Immunology, 2021)
Acute kidney injury (AKI) is a common and important feature of severe malaria, being an independent risk factor for death. Previous research has suggested that an overactivation of the host inflammatory response is at least partly involved in mediating the renal damage observed in P. falciparum patients with AKI, however the exact pathophysiology of AKI in severe malaria remains unknown. The purpose of this mini-review is to describe how different aspects of malaria pathology, including parasite sequestration, microvascular obstruction and extensive intravascular hemolysis, interact with each other and contribute to the development of AKI in severe malaria, by amplifying the damaging effects of the host inflammatory response. Here, we highlight the importance of considering how the systemic effects and multi-organ involvement of malaria are intertwined with the localised effects on the kidney.